Optimization of Process Variables on Ethanol Production from Sorghum Grain - Amin, M. Nur Ghoyatul; Hidayati, Darimiyya; Indarto, Cahyo (Fakultas Teknologi Pertanian Universitas Brawijaya, 2012)
This research was aimed for obtaining high level of yield in ethanol production from sorghum grain (Sorghum bicolor L.). Response surface methodology (RSM) is selected to optimize the process variables in ethanol production by employing Box Behnken design. The factors consist of Ammonium sulfate concentrations, shaking rates, and fermentation times, which are designed at 0%, 0.2%, 0.4%, 0 rpm, 50 rpm 100 rpm, 56 hours, 64 hours, 72 hours respectively. Second order polynomial model was developed by Design expert 07 to estimate the ethanol yield by different level for each factor and the regression square was 90.09%. Optimal solution in this work was determined by contour plot, with the highest yield was 39.55%(v/w) by combination of ammonium sulfate concentration, shaking rate, fermentation time are 0%, 31.69 rpm, 72 hours respectively.Keywords: box behnken, Fermentation, yield